TRPC3 channels play a critical role in the theta component of pilocarpine-induced status epilepticus in mice - Phelan, Kevin D. (2017)
Fil: Phelan, Kevin D. University of Arkansas for Medical Sciences. Department of Neurobiology and Developmental Sciences; Estados Unidos